Contaminated Waters: A Comprehensive Review of Heavy Metal Pollution in Marine Fish and Its Health Risks - Kurniasih Titin; Panigoro Novita; Panigoro Husain; Waryat; Ediwarman; Sutisna Ena; Fitria Yuliana; Arianto (BIO Web of Conferences)
Marine fish are crucial for the global food supply, providing essential nutrients to millions of people throughout the world. However, the presence of high levels of heavy metals in marine fish has become a significant risk to both human health and the sustainability of the fishing industry. This article is to provide a concise overview of recent scientific studies on the presence of heavy metals in marine fish products and the potential consequences for human health. The examination encompasses a range of frequently encountered heavy metals, along with the factors that affect the levels of pollution. This review also explores the geographical distribution of contaminated fish, pinpointing areas with high levels of contamination that necessitate focused attention. This study utilizes an comprehensive literature search technique by searching databases with the inclusion criteria of comprising relevant and recently published studies. The extracted data comprises information on the degrees of contamination, the fish species that are affected, and the health consequences that arise from consuming infected fish. This article also emphasizes the necessity for further research to address existing knowledge gaps and develop more efficient technologies and policies for managing heavy metal contamination in marine environments.